Cardiac arrest during spinal anesthesia for cervical conization: a case report. Issue 5 (29th March 2016) - Shinohara, Satoshi; Sakamoto, Ikuko; Numata, Masahiro; Ikegami, Atsushi; Teramoto, Katsuhiro; Hirata, Shuji
Key Clinical Message: Spinal anesthesia is regularly performed worldwide and is an integral part of the modern day anesthesia practice. Although unexpected cardiac arrests during this procedure are very rare, medical professionals should be aware of the potential for this complication. In making the decision to use spinal anesthesia, judicious patient selection, adequate preventive measures, and strict monitoring are important. Abstract : Spinal anesthesia is regularly performed worldwide and is an integral part of the modern day anesthesia practice. Although unexpected cardiac arrests during this procedure are very rare, medical professionals should be aware of the potential for this complication. In making the decision to use spinal anesthesia, judicious patient selection, adequate preventive measures, and strict monitoring are important.